STATIC MODELING OF A AND B RESERVOIR, LOWER SIHAPAS FORMATION, DJ FIELD, CENTRAL SUMATERA BASIN - Fadila Jusna , Nurul
The DJ petroleum field is located at Tebing Tinggi Barat District, Meranti Islands District, Riau Province, Indonesia with an area of Ã‚Â± 25 km2. Geologically, the DJ Field is located at the Tertiary Basin of Central Sumatra. Geological studies and reservoir modeling in this study focused on the Lower Sihapas Formation with two reservoir intervals marked by sandstone as its lithology. This study aims to determine reservoir characteristics especially facies type, sequence stratigraphy, and petrophyscal properties, also determine distribution reservoir and estimate the amount of hydrocarbon reserves. Checkshot, well log, seismic (3D), and description from side wall core were the data used in this research. Methods applied in this research were well data analysis which includes correlation of Sequences Stratigraphy and petrophysical analysis; seismic data analysis which includes lithofacies analysis, electrofacies, facies association, sequence stratigraphy, petrophysical analysis, static 3D reservoir modeling, and OOIP The outcome produced an analysis of the geological conditions and the amount of hydrocarbon volumetric Side rock core analysis showed that lithofacies forming Lower Sihapas Formation aggregate five litofacies. Based on geometry analysis, microfossil analysis, lithofacies analysis, electrofacies, the research took place in estuary environment with intertidal sand bar, estuarine channel, and mud flats facies associations. The main geological structure of the DJ Field is anticline and normal fault that has north-western trending. The distribution of reservoir property was controlled by facies distribution and deposition directing from northeast-southwest. The estimation of hydrocarbon reserves in place at both reservoir intervals in the study area is 18 million STB.